Relación entre los factores de riesgo psicosocial y la resistencia al cambio organizacional en personal de seguridad de una empresa del sector económico terciario (2007)
In this investigation the relation between the factors of psycho-social risk and the resistance to the change in the personnel of security of an organization of the tertiary economic sector of benefit of services was identified. It was made under a corelational cross-sectional design, through the application of the measuring instruments of resistance to the change (IMRC) and measurement of psycho-social risk (IMP). The established phases were: a) compilation of the information, document analysis and elaboration of measuring instrument of the resistance to the change, b) validation of both instruments by judges, c) establishment of contacts and pertinent authorizations to make the application pilot, d) application of both measuring instruments to collect the information necessary to carry out the corelational analysis and e) data analysis and presentation of the results report. The instruments were applied to 199 people who fulfilled the characteristics of the study. The results were analyzed with SPSS-13. It was find a 0.605 corelation with trustworthiness of 84% for change resistances, and 0.79 for psycho-social risk. These indices surpass the minimum of 0.50 established, which indicates a high level of trustworthiness and precision in the measurement of the attribute, this allows to predict a high level of trustworthiness in the evaluation of the variables in other applications. Between the most important implications of the study they are the necessity to extend the investigation to other elements related to the survival and growth of the organizations and confirmation of another battle area for the psychologist. Key words: Pycho-social risk factors, change, resistance to change.